Evaluation of a self-instructional self-regulated learning material in mathematics - Balan, Andreia; Jönsson, Anders (Frontiers in Education, 2025)
Success in school is closely linked to students’ ability to regulate their own learning. In mathematics, self-regulated learning (SRL) strategies can help students become more independent and proactive in their learning. However, there is limited research on how students can be effectively supported in developing and applying these strategies, especially for younger students. The purpose of this study is to evaluate the impact of a self-instructional SRL material. The material is designed in collaboration between researchers and teachers, and integrated into regular mathematics instruction. Specifically, we examine whether the use of the SRL material varies across schools and student groups. A quasi-experimental research design with pre- and post-tests was employed, involving 258 students in grades 5 and 6 from five different schools over the course of one semester. Data was collected through structured surveys measuring student engagement with the material, along with performance tracking before and after the intervention. The findings indicate that co-developing SRL materials with teachers, and embedding them in regular instruction, has clear advantages. The findings also show that while the material was used equally across genders and performance levels, variations remain due to school culture, socio-economic factors, and individual teacher influence. Notably, lower-performing students showed greater progress compared to high-performers, and girls engaged more actively with SRL strategies than boys. These findings have important implications for the design and implementation of SRL interventions. While integrating SRL support within everyday teaching fosters engagement, additional measures may be needed to address persistent disparities between schools and student groups.